Iconological Analysis of the Peranakan Intimate Lifestyle: A Case Study of Sylvia Lee Goh’s Woman, Oh! Woman Painting Series - Eddy Izuwan Musa; Sarena Abdullah (Wacana Seni Journal of Arts Discourse, 2017)
The Peranakan Chinese, sometimes known as the Baba Nyonya, are known for their hybrid culture. Most studies on the Peranakan examine the architectural heritage, material culture and cuisine; there is limited focus on the study of visual artworks of the Peranakan. This paper explores and analyses a painting series entitled, "Woman Oh! Woman Series" by Sylvia Lee Goh, a descendant of a Peranakan family in Kedah, who works predominantly in producing Nyonya-themed paintings. This paper provides a deeper reading of this series by drawing on Panofsky's theory of iconography and iconology as a tool in discussing these artworks within the larger context of Peranakan culture. Through Panofsky's three stages of iconography, this paper explores how the four artworks in the "Woman Oh! Woman Series" could be read through three main significant trajectories in parallel with the Peranakan ethos—the persistence of nature veneration against mortality and ancestor worship, refined etiquette and gender roles, and camaraderie and communal guest reverence.